Exploring Islamic Extracurricular Mediation: The Impact of Islamic Religious Education Learning and Peers on Spiritual Quotient - Putri, Nabila Raessal Manda; Daryono, Rihab Wit (EDUKASIA, 2023)
This study aims to examine the effect of Islamic religious education learning and peers on students' spiritual Quotient and the mediating role of Islamic extracurriculars in the relationship between the two variables. The research method used is a quantitative approach with a survey method to examine the construction of students' spiritual Quotient variables. This study used a purposive sampling. The data collection technique was carried out through a questionnaire with four variables using a Likert scale. The results showed that Islamic religious education learning has a positive but insignificant influence on students' Spiritual Quotient. On the other hand, peers and Islamic extracurriculars have a positive and significant influence on spiritual Quotient. The implications of the study show that Islamic religious learning needs to be supported by extracurricular activities and religious programs in schools. Research recommendations include strengthening extracurricular programs, regular monitoring, and increasing the involvement of learners who do not participate in extracurricular activities. This is expected to improve the overall spiritual Quotient of all learners.